Basophil Reactivity as Biomarker in Immediate Drug Hypersensitivity Reactions—Potential and Limitations - Steiner, Markus; Harrer, Andrea; Himly, Martin (Frontiers in Pharmacology, 2016)
Immediate drug hypersensitivity reactions (DHRs) resemble typical immunoglobulin E (IgE)-mediated symptoms. Clinical manifestations range from local skin reactions, gastrointestinal and/or respiratory symptoms to severe systemic involvement with potential fatal outcome. Depending on the substance group of the eliciting drug the correct diagnosis is a major challenge. Skin testing and in vitro diagnostics are often unreliable and not reproducible. The involvement of drug-specific IgE is questionable in many cases. The culprit substance (parent drug or metabolite) and potential cross-reacting compounds are difficult to identify, patient history and drug provocation testing often remain the only means for diagnosis. Hence, several groups proposed basophil activation test (BAT) for the diagnosis of immediate DHRs as basophils are well-known effector cells in allergic reactions. However, the usefulness of BAT in immediate DHRs is highly variable and dependent on the drug itself plus its capacity to spontaneously conjugate to serum proteins. Stimulation with pure solutions of the parent drug or metabolites thereof versus drug-protein conjugates may influence sensitivity and specificity of the test. We thus reviewed the available literature about the use of BAT for diagnosing immediate DHRs against drug classes such as antibiotics, radio contrast media, neuromuscular blocking agents, non-steroidal anti-inflammatory drugs, and biologicals. Influencing factors like the selection of stimulants or of the identification and activation markers, the stimulation protocol, gating strategies, and cut-off definition are addressed in this overview on BAT performance. The overall aim is to evaluate the suitability of BAT as biomarker for the diagnosis of immediate drug-induced hypersensitivity reactions.